Macroscopic self-propelled objects - Zhao, Guanjia (2013)
Self-propelled systems are currently in the spotlight of the research community. We review the progress of the construction of both millimeter- and centimeter-sized self-propelled macroscopic objects. We will also discuss the various sources of energy used by these systems, such as the electromagnetic field, electric field, thermal gradient, and chemical energy, and present how these millimeter- and centimeter-sized devices can move at velocities of tens cm s−1 and distances of several tens of meters.